Cytotoxic biphenyl-4-carboxylic acid targets the tubulin–microtubule system and inhibits cellular migration in HeLa cells. Issue 6 (1st October 2016) - Mukherjee, Suman; Chatterjee, Shamba; Poddar, Asim; Bhattacharyya, Bhabatarak; Gupta, Suvroma
Abstract: Two structurally similar biphenyl compounds, biphenyl-2-carboxylic acid (B2C) and biphenyl-4-carboxylic acid (B4C), were selected to assess their cellular cytotoxic and antimitotic behaviour in the quest of a potent anticancer compound. The HeLa and MCF-7 cell lines were used to determine the cytotoxic effect of the two biphenyl compounds using the MTT assay. Confocal microscopy was performed to analyze the degree of nuclear condensation and fragmentation associated with depolymerized microtubules that result from inhibiting in vitro tubulin polymerization. Circular dichroism spectroscopy along with DTNB kinetics were conducted to predict alterations in the tubulin secondary structure and global conformational changes in the tertiary structure of the protein, respectively. Finally, a wound healing assay was employed to assess whether cellular migration was inhibited in the treated HeLa cells. B4C imparted more cellular cytotoxicity in the HeLa and MCF-7 cell lines (IC50 ∼ 4 μM). B4C inhibited in vitro tubulin polymerization into microtubules with an IC50 of 50 μM. Confocal microscopy of treated cell indicated presumptive apoptosis, exhibiting fragmented nuclei with significant microtubular disruption, which was confirmed by Western blot analysis. Circular dichroism revealed a significant reduction in the α-helix content of treated tubulin. DTNB kinetics showed that approximately six –SH groups were buried in the structure. The wound healing assay revealed that B4C prevented cellular invasion. B4C had greater cytotoxic and antimitotic effects against HeLa cells than B2C. To delineate the specific mechanism of action of B4C and its derivatives, further research is warranted.